Implementasi Kebijakan Undang-Undang Nomor 24 Tahun 2011 tentang Sistem Jaminan Sosial Nasional terhadap Penggunaan Mobile JKN di Puskesmas Maiwa - Nur Zahira; Harianti Hamid; Sundari, Sundari; Muhammad Nur (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the implementation of policies on the national social security system on the use of Mobile JKN in the Maiwa Health Center. The population in this study is 22,791 participants who are registered JKN participants in 2024. The sampling technique used random sampling of 100 respondents. This type of research is quantitative deductive. The data collection techniques used in this study were observation, questionnaire, and literature study. The data analysis technique used was a validity and reliability test using the help of the IBM SPSS statistical 26.0 application. The results of this study show that there is a strong relationship between the implementation of "influential/significant" policies on the use of Mobile JKN in the Maiwa Health Center. Based on the results of the recapitulation of the Policy Implementation variable with a percentage result of 68% in the good category and the recapitulation of the variable of Mobile JKN Use with a percentage result of 71.7% in the good category. The factors that affect the use of Mobile JKN with a percentage result of 65% are in the good category. The results of the ANOVA Test analysis were obtained by Fcal of 114,848 with a significant level of 0.000, this shows that independent variables have a significant effect and the probability is far above 0.05 partial thcal (10,717) > ttable (1.661), meaning that the implementation of the policy "has a significant effect" on the Use of Mobile JKN at the Maiwa Health Center.